Methodología Strategies for improving listening skill - Veintimilla Veintimilla, Fátima Jahaira (2017)
The listening skill is important because it is a mental process that involves a focus of attention to what is heard. The objective of this research work is to diagnose the methodological strategies for improving listening skill. Nowadays, there are students who cannot cope with audio content found on listening activities as well as general understanding of ideas and messages that are part of extracts in textbooks. In such terms, this research work embraces the diagnosis of methodological strategies when practicing listening to determine if students from 5th, 6th, and 7th grade EBG at International Cotopaxi School use them to improve this ability. This research was conducted through a descriptive methodology in which the outcome shows an analysis about listening strategies and aspects in which students have more difficulties with. Subsequently, a survey was applied in order to gather information. It was applied to students and there was a sample of 28 students coming from “International Cotopaxi” School. Bearing in mind students’ criteria, findings reveal that teachers are only using audio from books and do not add new methodological strategies which promote the development of listening. In addition, there is evidence showing that listening is the less practiced skill in language classrooms. Then, according to the data, it can be asserted that songs, videos, are activities to be implemented as a must do at English lessons since they were strong options of choice for students. To conclude, the impact of this study is centered on future researchers who can make use of this research work to come up with proposals regarding adequate methodological strategies to develop listening on students from primary school.